THE STUDY OF NATURE OF FISH ASSEMBLAGE IN AL-SAFFIA RESERVATION, AL-HAWAIZAH MARSHES, IRAQ. - Younis, K. H.; Al-Mukhtar, M. A.; Al-Katrani, L. M.; Abdullah, A. J.; Abdullah, S. A. (Iraqi Journal of Aquaculture, 2022)
The study include the description of fish assemblage in Al- Saffia reservation during the period March 2006 to February 2007. Sixteen of osteichthyes species were obtained, the highest number of species 13 was recorded during July and the lowest 7 in November and January. The largest number of individuals collected was obtained during July (212) and the lowest in February (124). Four species formed 71.02% include Alburnus mossulensis 20.64 % Liza abu19.62 % Barbus luteus16.13 % Carassius auratus 14.46 %. The annual values of richness (D), diversity (H) and evenness (J) were 1.95 , 2.12 and 0.76 respectively .